Co-Metabolic Degradation of β-Cypermethrin and 3-Phenoxybenzoic Acid by Co-Culture of Bacillus licheniformis B-1 and Aspergillus oryzae M-4 - Zhao, Jiayuan; Chi, Yuanlong; Xu, Yingchao; Jia, Dongying; Yao, Kai (PLOS ONE, 2016)
The degradation efficiency of organic contaminants and their associated metabolites by co-culture of microbes is mainly limited by toxic intermediates from co-metabolic degradation. In this study, we investigated the degradation of β-cypermethrin (β-CY) and 3-phenoxybenzoic acid (3-PBA) by co-culture of Bacillus licheniformis B-1 and Aspergillus oryzae M-4, as well as the influences of β-CY and 3-PBA metabolites on their degradation and the growth of strains B-1 and M-4. Our results indicated that 100 mg/L β-CY was degraded by 78.85%, and 3-PBA concentration was 0.05 mg/L after 72 h. Compared with using only strain B-1, the half-life (t1/2) of β-CY by using the two strains together was shortened from 84.53 h to 38.54 h, and the yield coefficient of 3-PBA was decreased from 0.846 to 0.001. At 100 mg/L of 3-PBA and gallic acid, β-CY and 3-PBA degradation were only 17.68% and 40.45%, respectively. As the toxic intermediate derived from co-metabolic degradation of β-CY by strain B-1, 3-PBA was efficiently degraded by strain M-4, and gallic acid, as the toxic intermediate from co-metabolic degradation of 3-PBA by strain M-4, was efficiently degraded by strain B-1. These results provided a promising approach for efficient biodegradation of β-CY and 3-PBA.